2017
DOI: 10.1177/0734242x17726164
|View full text |Cite
|
Sign up to set email alerts
|

Support for designing waste sorting systems: A mini review

Abstract: This article presents a mini review of research aimed at understanding material recovery from municipal solid waste. It focuses on two areas, waste sorting behaviour and collection systems, so that research on the link between these areas could be identified and evaluated. The main results presented and the methods used in the articles are categorised and appraised. The mini review reveals that most of the work that offered design guidelines for waste management systems was based on optimising technical aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 58 publications
(181 reference statements)
0
38
0
5
Order By: Relevance
“…In line with existing calls for multidisciplinary research, from Rousta et al [106] among others, the reviewed literature revealed that in order to support sustainable development and increase the amount of products reduced and reused, material recycled and resources recovered from waste, multidisciplinary research is needed to scientifically identify sustainable interventions aimed the waste management system, as well as the people that participate in it. Future research should focus on learning from the experiences that people make when they are new to a waste management scheme, and what the meaning of these experiences are.…”
Section: Discussionmentioning
confidence: 88%
“…In line with existing calls for multidisciplinary research, from Rousta et al [106] among others, the reviewed literature revealed that in order to support sustainable development and increase the amount of products reduced and reused, material recycled and resources recovered from waste, multidisciplinary research is needed to scientifically identify sustainable interventions aimed the waste management system, as well as the people that participate in it. Future research should focus on learning from the experiences that people make when they are new to a waste management scheme, and what the meaning of these experiences are.…”
Section: Discussionmentioning
confidence: 88%
“…Accessibility is a crucial factor for successful recycling [31]. Local conditions are important when choosing a collection system and convenience is key [32]. Kerbside collection is a key element to improve waste management [33].…”
Section: Type Of Change/comparison and In What Countrymentioning
confidence: 99%
“…Especially the connection between technology, social-cultural influences and human behavior is a crucial cross-road of academic studies that in collaboration can help the separate collection concept to become a successful system of the circular economy. 8 Instead of asking people to sort their waste, one may also use automated technology to sort mixed waste at the recycling plant. This concept continues the mixed waste collection system, though shredding and high compaction in the waste truck can no longer be allowed for obvious reasons.…”
Section: Waste Collection Systemsmentioning
confidence: 99%